WIDEBAND X-BAND ANTENNA DESIGN FOR FIGHTER RADAR - S. Lumban Raja, Erick
Radar installed on fighter aircraft requires a large gain and a radiation pattern with the main beam direction in the same direction as the length of the antenna or perpendicular to the front. In this thesis, the design, simulation and fabrication of the antipodal Vivaldi antenna were carried out. Using the microstrip line and power divider/combiner supply method for an antenna array consisting of 64 elements. The antenna is designed for X-band fighter radar applications working in the 9-9.5 GHz frequency range. The dielectric material used is FR-4 Epoxy with a relative permittivity of er = 4.3 and a substrate thickness of h = 1.6 mm and an antenna patch thickness of t = 0.035 mm. The measurement results show that at a frequency of 9.25 GHz the antenna can work well with return loss and VSWR values of -33.8315 dB and 1.042 respectively. The resulting impedance bandwidth is more than 4 GHz in a frequency range of less than 8 GHz to more than 12 GHz and has a gain of 16.939 dBi at a frequency of 9.25 GHz. The antenna parameters from the measurements have values that are close to the simulation results. The results of manufacturing an 8×8 array antenna have dimensions of 267 mm × 139 mm × 99 mm.